BCL-XL directly modulates RAS signalling to favour cancer cell stemness - Sophie de Carné Trécesson (Nature Portfolio, 2017)
BCL-XL provides a survival advantage to cancer cells even in the absence of apoptotic pressures. In this study, the authors show that BCL-XL interacts with RAS in a BH4-dependent manner and regulates RAS-mediated activation of pathways involved in the stemness feature of breast cancer cells.